Influence of Nucleated Cells of Human Cord Blood on Indices of Immune System of Animals with Atopic Dermatitis - Goltsev, Anatoliy; Koval, Hanna; Bondarovych, Mykola; Lutsenko, Olena; Ostankov, Maksym (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):310